Perilaku Suami terhadap Istri yang Nusyuz Perspektif Syafiq Riza Basalamah - Wahidah, Fida Zakiah; Irsan, Irsan (Institut Agama Islam Ngawi, 2024)
Wife's nusyuz (disobedience) is something that can invite hatred between husband and wife which results in a violation of commitment in carrying out rights and obligations. Husbands' behavior towards nusyuz (disobedient) wives often becomes a serious problem in the household because the husband's inappropriate behavior in dealing with nusyuz results in greater conflict and often ends in divorce. The researcher chose the perspective of Syafiq Riza Basalamah, because he is a famous preacher who is known as an observer of Muslim family issues through lectures on social media. The research method used is library research with a qualitative approach. The aim of this research is: to find out the factors that cause nusyuz and Syafiq Riza Basalamah's perspective regarding husbands' behavior towards nusyuz wives. The results of this research show that: factors causing nusyuz, a) lack of understanding of religion, b) gender equality, c) third person (affair), d) husband not carrying out his obligations, e) prolonged conflict and lack of communication. Syafiq Riza Basalamah's perspective on the behavior of husbands towards nusyuz wives, a) giving advice, b) separating the beds, c) beatings that don't hurt, d) bringing in a mediator. Keywords: Husband's behavior, Nusyuz wife, Syafiq Riza Basalamah.